ANTHROPOMETRIC STUDY IN DEUTERO-MALAY ETHNIC IN SEARCH OF ACCURATE HEIGHT FORMULAS FOR NUTRITIONAL STATUS ASSESSMENT (Proceedings of the International Conference on Public Health, 2017)
Nutritional status can be assessed using a person’s height. Sometimes it is difficult to quantify for example in bedrest patient or abnormal stature, so it needs an alternative anthropometric measurement, such as height estimation based on long-bones measurement. Little information is available about the accuracy of these measurements, especially in deutero-malay ethnic. The present study aimed to compare accuracy for estimating height from several long-bones lengths to search an accurate anthropometric formula for nutritional status assessment. This study used an observational analytic method with cross sectional approach. The samples are students of Medical Faculty of University of Jember that meet the inclusion and exclusion criteria. Data were analyzed with Kolmogorov-Smirnov test, Pearson Correlation test and linear regression. The method is by measuring height with microtoise and bones length with medline. The result showed strong and positive (r > 0.5) correlation between height and length of long-bones, so linear regression can be done. Among ulna, femur, humerus and radius bones, femur formula showed the highest accuracy both in men (r right = 0.904; left =0.906) and women (r right = 0.911; left = 0.900). We conclude that anthropometric formula from estimation of height by length of femur is the most accurate from all formula, thus the most preferable to be used for height estimation in deutero-malay ethnic when assessing nutritional status.
Keywords: anthropometric formulas, height estimation, nutritional status, deutero-malay